THE COURT EXPERT AS A MEANS OF EVIDENCE IN THE LITIGATION PROCEEDINGS - Nacev, Vlatko; Belovski, Vojo (Journal of process management and new technologies, 2018)
The expertise as one of the legally defined means of evidence in litigation proceedings is an unavoidable procedural action without any litigation procedure can be successfully completed in the merits. The expertise is usually implemented in order to answer a specific factual subject important for making legal and precise decision about litigation proceedings. In the case of deciding about the implementation of legal form, the expertise is not applied and required. There are a lot of opinions in the practice that the work of the expert witnesses is not at an appropriate and satisfied level related to the standards and criteria for an independent and efficient judiciary system. This is characterized especially in the countries where the justice system is unstable and completely not independent of the political and social influences, such as many other external and internal factors. In these countries, as the Republic of Macedonia, the expertise is also emphasized with subjective nature, where the findings and opinions are considered as insufficiently specialized and unprofessional. However, there are exceptions to this rule. The court practice shows that there are court experts who perform their activities honestly, morally and professionally. Taking into consideration the great importance that court experts have with their findings and opinions in the litigation procedure, they have an influence on this complex process with their findings and opinions as legal evidence. The court expertise, as means of proof in litigation, has a big importance. The judicial review as a means of proof in the litigation procedure is performed when in order to establish the facts or to clarify some of the particular circumstances a direct examination and observation by the court is required. That’s why the court experts are distinguished as skillful persons who have professional knowledge, which is necessary for the court to verify the truth of certain assumptions and facts presented in front of the court form both sides.